1995
DOI: 10.1080/07315724.1995.10718483
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and the common cold: a retrospective analysis of Chalmers' review.

Abstract: Problems in influential reviews on vitamin C and the common cold are discussed also in:Hemilä H. Vitamin C supplementation and common cold symptoms: problems with inaccurate reviews. Nutrition 1996;12:804-809 http://dx.doi.org/10.1016/S0899-9007(96)00223-7 http://hdl.handle.net/10250/7979 Manuscript version with links to references added.In his review, Chalmers put a great weight on the Karlowski (1975) study. However, the Karlowski study was shown to be erroneously analysed in 1996: Hemilä H. Vitamin C, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 42 publications
2
68
1
3
Order By: Relevance
“…3. The Anderson 1974 study (17) with adults is excluded from Table 1, since there is evidence of biased distribution of subjects in the eight study groups (5,17). The Carson 1975 study (20) with adults administered 1 g/day is excluded, since the authors were interested solely in the possibility of there being an effect on the incidence of colds, and not on the severity of symptoms, so that appropriate data are not available.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3. The Anderson 1974 study (17) with adults is excluded from Table 1, since there is evidence of biased distribution of subjects in the eight study groups (5,17). The Carson 1975 study (20) with adults administered 1 g/day is excluded, since the authors were interested solely in the possibility of there being an effect on the incidence of colds, and not on the severity of symptoms, so that appropriate data are not available.…”
Section: Methodsmentioning
confidence: 99%
“…In placebo-controlled studies, regular vitamin C supplementation ( 1 g/day) has consistently decreased morbidity due to the common cold (1)(2)(3)(4)(5)(6)(7)(8). While the biochemical basis of this effect is not well understood, vitamin C does have diverse effects on the immune system (3,5,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Chalmers' review was shown to contain serious errors (16). For example, in some cases the data presented were inconsistent with the originally published results.…”
Section: Chalmers' 1975 Reviewmentioning
confidence: 94%
“…Anderson et al's (5) 1972 study was included in the table as the dose during the episodes was 4 g/d although the regular dose was only 1 g/d. Anderson's 1974 study was excluded since there is bias in the distribution of subjects in the study groups (15,16). For the studies by Anderson et al (5) and Pitt and Costrini (12), the days indoors and severity of symptoms, respectively, were selected as outcomes in the calculations.…”
Section: Introductionmentioning
confidence: 99%